Real-time simulation of a fragmenting explosion for cylindrical warheads. (October 2022) - Felix, David; Colwill, Ian; Harris, Paul
Explosion models based on finite element analysis (FEA) can be used to simulate how a warhead fragments. However, their execution times are extensive. Active protection systems need to make very fast predictions, before a fast attacking weapon hits the target. Fast execution times are also needed in real-time simulations where the impact of many different computer models is being assessed. Hence, FEA explosion models are not appropriate for these real-time systems. As a trade-off between accuracy and execution time, this paper creates a simulation of fragments from a warhead's explosion, using simple analytical equations. The results are verified against explosion experimental data and FEA results. The developed model then can be made available for real-time simulation and fast computation.